The Role of Succession Firm in CSR Disclosure Manufacturing Companies Listed on IDX 2018-2022 - Haryanto, Hery; Candy, Candy; Liana, Jumi (Program Studi Akuntansi FPEB UPI, 2024)
This study aims to analyze the influence of family firm succession on corporate social responsibility (CSR). A sample was drawn from manufacturing companies listed on the Indonesia Stock Exchange, comprising 147 firms, equivalent to 735 data points from the years 2018 to 2022, meeting the required criteria. A quantitative approach was employed as the research method to identify relationships and effects among variables, specifically family firm succession on corporate social responsibility (CSR). Companies meeting the family firm criteria were measured using a nominal scale in the form of dummy variables, while the disclosure of social responsibility was assessed using the Global Reporting Initiative (GRI) indicators. Data analysis was conducted using Stata software, applying descriptive statistical methods and OLS regression. The findings of this research testing are consistent with prior studies, indicating decrease in CSR levels during leadership transitions within family firms.